2005
DOI: 10.1103/physreve.72.031809
|View full text |Cite
|
Sign up to set email alerts
|

Collective motion in Poly(ethylene oxide)/poly(methylmethacrylate) blends

Abstract: We present neutron spin echo and structural measurements on a perdeuterated miscible polymer blend: poly(ethylene oxide)[PEO]/poly(methyl methacrylate)[PMMA], characterized by a large difference in component glass transition temperatures and minimal interactions. The measurements cover the q range 0.35 to 1.66 A(-1) and the temperature range Tg -75 to Tg +89 K, where Tg is the blend glass transition. The spectra, obtained directly in the time domain, are very broad with stretching parameters beta approximately… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
47
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 41 publications
(51 citation statements)
references
References 45 publications
4
47
0
Order By: Relevance
“…This behavior of this process is consistent with previous observations: the primary relaxation of PMMA is significantly influenced by environment, while that of PEO is not. [30][31][32][33][34][35][36][37] In particular, the observation that PEO mobility is slowed slightly when mixed with PMMA, with the extent independent of composition is consistent with deuterium NMR experiments on this system. 31 To summarize the decays for the entire temperature and spatial scale range of our simulations, we extract a characteristic time from I PEO (q,t) or I PMMA (q,t) using the empirical KolrauschWilliams-Watts [KWW] expression:…”
Section: Simulation Detailssupporting
confidence: 71%
“…This behavior of this process is consistent with previous observations: the primary relaxation of PMMA is significantly influenced by environment, while that of PEO is not. [30][31][32][33][34][35][36][37] In particular, the observation that PEO mobility is slowed slightly when mixed with PMMA, with the extent independent of composition is consistent with deuterium NMR experiments on this system. 31 To summarize the decays for the entire temperature and spatial scale range of our simulations, we extract a characteristic time from I PEO (q,t) or I PMMA (q,t) using the empirical KolrauschWilliams-Watts [KWW] expression:…”
Section: Simulation Detailssupporting
confidence: 71%
“…In addition, we note that results obtained on IN11C (IN11 with a multidetector option) on deuterated PMMA below T g (at 393 K) display a slight quasielastic decay. 20 In that study the T dependence of the relaxation times around T g was found to be very similar to that of the -process. On the other hand, we recall that 2D-NMR data on the PMMA side-group motion by Schmidt-Rohr et al 11 showed that the main-chain and the ester side-group dynamics of this polymer are coupled.…”
Section: S S H Sg (Qt) By S I (Qt) ) S H Mc (Qt)/a H Mc (Q) the Rmentioning
confidence: 81%
“…The second work 8 did not report on the homopolymer dynamics. Finally, in the neutron spin-echo study on collective motion, 20 the temperature range was restricted to only two temperatures very close to T g for pure PMMA.…”
Section: Introductionmentioning
confidence: 99%
“…These times have been extracted using the Kolraush-Williams- (9) QENS slow process data for the 20% blend at Q ) 1.3 Å -1 (this work), (b) QENS fast process data for the 20% blend at Q ) 1.3 Å -1 (this work), (×) dielectric spectroscopy data for the R-relaxation of neat PEO, 11 (+) dielectric spectroscopy data for the -relaxation of PEO in a 20% blend, and (-) dielectric spectroscopy data for the γ-relaxation of PEO in a 20% blend. 11 Watts 41 The relaxation times show no sign of a modulation with Q, but rather the -2/ scaling with a spatial scale characteristic of incoherent relaxation times 44 is observed. The characteristic times obtained without accounting for an elastic fraction are similar for the 20% and 30% blends, which is consistent with prior measurements on this system.…”
Section: Resultsmentioning
confidence: 99%